2004
DOI: 10.1027/1015-5759.20.2.116
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Color on Emotions in the Holtzman Inkblot Technique

Abstract: In this study, the influence of chromatic and achromatic color on emotions in the Holtzman Inkblot Technique (HIT) was tested empirically. Samples of normals (n = 30), patients with neurotic disorders (n = 30), borderline patients (n = 30), and both acute (n = 25) and chronic schizophrenics (n = 25) were studied with the HIT. A computerized investigation of verbally expressed emotions was performed by means of the “Affective Dictionary Ulm” (ADU; Dahl, Hölzer, & Berry, 1992 ), which was applied to the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study thought disordered responses showed a negative correlation with structural ambiguity and a positive correlation with interpretative ambiguity. In a previous study, the number of emotion words given in response to a HIT card also correlated significantly negatively with structural ambiguity in nonschizophrenic groups (Leichsenring, 2004). However, for another indicator of personality functioning, the avoidance of ambiguity, an inverse relation seems to be characteristic (Leichsenring & Meyer, 1994): HIT cards of high structural ambiguity elicited significantly more avoidance of ambiguity as assessed by the applied computerized lexical-content analytic method (in normals, patients with neurotic disorders, borderline patients, and acute schizophrenics).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study thought disordered responses showed a negative correlation with structural ambiguity and a positive correlation with interpretative ambiguity. In a previous study, the number of emotion words given in response to a HIT card also correlated significantly negatively with structural ambiguity in nonschizophrenic groups (Leichsenring, 2004). However, for another indicator of personality functioning, the avoidance of ambiguity, an inverse relation seems to be characteristic (Leichsenring & Meyer, 1994): HIT cards of high structural ambiguity elicited significantly more avoidance of ambiguity as assessed by the applied computerized lexical-content analytic method (in normals, patients with neurotic disorders, borderline patients, and acute schizophrenics).…”
Section: Discussionmentioning
confidence: 69%
“…Another study showed that HIT cards of high structural ambiguity elicited less emotions in normals, patients with neurotic disorders, and borderline patients (Leichsenring, 2004). According to these results, structural and interpretative ambiguity seems to be correlated differently with indicators of psychopathology.…”
mentioning
confidence: 99%